Phosphorylation mediated events in biomarker discovery for Alzheimer’s disease - Oliveira, Joana Machado de (2021)
Alzheimer´s disease (AD) is one of the most common forms of dementia worldwide; representing 60-70% of all dementia cases. This neurodegenerative disorder is characterized by the presence of senile plaques (SPs), neurofibrillary tangles (NFTs) and synaptic loss. Amyloid-β peptide (Aβ), the major constituent of SPs, is a fundamental player in AD, since it can trigger several pathogenic events such as neurotoxicity and activation of inflammatory and apoptotic cascades. All these events associate with neurodegeneration and consequently gradual cognitive decline are evident in AD patients. Abnormal phosphorylation is accepted as one of the key signaling transduction mechanism involved in AD pathogenesis. In fact, several studies have reported abnormal protein kinase and protein phosphatase activities in AD brains as well as abnormal phosphorylation levels of both amyloid precursor protein (APP) and Tau protein, two proteins in the genesis of SPs and NFTs. This thesis aimed to address how phosphorylation mediated events could impact the neuronal phosphoproteome, thereby unravelling novel disease molecular targets. To achieve this, two distinct models were employed: one using okadaic acid, a protein phosphatase inhibitor and a potent neurotoxin; and the other using the neurotoxic Aβ peptide as a relevant AD specific mimicking model. In both cases, several phosphoproteins were identified. Neuronal treatment with OA lead to the recovery of 245 phosphoproteins that significantly increased and 75 phosphoproteins that significantly decreased; while exposure to Aβ resulted in 73 phosphorylated proteins that increased, and 68 that decreased in response to peptide exposure. In addition, due to the key role played by Aβ in AD, its effect on the phosphorylation state of the two key proteins in AD, APP (at Thr668 residue) and Tau (at Ser262 and Ser396 residues), were also evaluated. Data shows that Aβ itself can impact the phosphorylation state of both proteins, and thus, by affecting APP phosphorylation and potential APP processing, it can contribute to its own production. Taken together these findings suggest that Aβ plays a fundamental role in abnormal protein phosphorylation, potentially leading to abnormal signaling cascades, and consequently contributing to AD pathology. Interestingly, this work also unravels several candidates that can contribute to our understanding of the molecular mechanisms underlying AD pathology, but more so it identified novel putative biomarker candidates that can open avenues for the development of future diagnostic and therapeutic tools.